"What Do You Think We Should Do?": Relationship and Reflexivity in Participant Observation. (July 2015) - Elliot, Michelle L.
This article uses three concepts as a framework by which to examine how the interrelational elements of ethnographic approaches to qualitative inquiry reflect dimensions of therapeutic engagement. Participant observation, reflexivity, and context are all widely and routinely included within research methods; however, they are less frequently attended to directly in their experiential capacity through the lens of the researcher, clinician turned investigator. A unique study design will be profiled to reflect the complicated juxtaposition between methods, questions, sample population, time, space, and identity. Studying occupational therapy students traveling abroad for a short-term immersion experience, this narrative study called on a necessary and attentive awareness of locality as the researcher traveled with the group. Conducting ethnographic research where the researcher's therapeutic skills aided and constrained relationships resulted in rich, guarded, and relevant insights that parallel the therapeutic use of self in occupational therapy practice.